2017
DOI: 10.4103/jmh.jmh_15_17
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality of life in breast cancer patients: A descriptive and cross-sectional study with review of literature

Abstract: Objective:This descriptive and cross-sectional study was undertaken to determine the factors affecting quality of life (QOL) in breast cancer patients.Methods:We collected data from 60 patients of carcinoma breast post modified radical mastectomy on radiotherapy in a tertiary care hospital. We included volunteered patients with a signed informed consent and at least 70 Karnofsky Performance Scale points. The data was gathered by interview technique using EORTC QLQ-C30 and QLQ-BR23 (Breast Cancer Module).Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 17 publications
(15 reference statements)
4
46
2
2
Order By: Relevance
“…(29) The positive impact of low stage of cancer has also been consistently reported by researchers across different populations of breast cancer patients. (29)(30)(31)(32) While Shen et al found that higher education increased QoL, our study showed that having a graduate or postgraduate education decreased QoL in the RP domain, when compared with having a secondary or below education level. (29) More importantly, our study highlighted that having supportive nurses at the time of diagnosis could positively influence a patient's SF.…”
Section: Resultscontrasting
confidence: 68%
“…(29) The positive impact of low stage of cancer has also been consistently reported by researchers across different populations of breast cancer patients. (29)(30)(31)(32) While Shen et al found that higher education increased QoL, our study showed that having a graduate or postgraduate education decreased QoL in the RP domain, when compared with having a secondary or below education level. (29) More importantly, our study highlighted that having supportive nurses at the time of diagnosis could positively influence a patient's SF.…”
Section: Resultscontrasting
confidence: 68%
“…Inhomogeneity of radiation dose distribution also caused severe radiation dermatitis. With conventional breast radiotherapy, a portion of the breast tissue receives 110% of the prescription dose, occasionally up to 120% (20). Chen et al reported that such hotspot with over 110% of the prescribed dose may be an important predictor for radiation dermatitis (12).…”
Section: Discussionmentioning
confidence: 99%
“…Research in the Western Countries found that the QOL of some patients with breast cancer is poor (Hong, Fu, & Mi, 2006;Setyowibowo et al, 2018;Sharma & Purkayastha, 2017;Zhao & Li, 2007). Setyowibowo et al (2018) reported that women with breast cancer symptoms had lower QOL than women from the general population, while Sharma and Purkayastha (2017) stated that younger women with breast cancer (30-39 years) had poor QOL levels on physical, social and emotional domains compared with older women (70-79 years). Patients who underwent breast-conserving surgery or modified radical mastectomy were found to have poor physical, emotional and functional well-being (Yu, Lu, & Liu, 2008).…”
mentioning
confidence: 99%